Design and fabrication of a cassava peeling machine (2005)
The varying shapes and sizes of cassava tubers have made cassava peeling to be one of the major problems in the mechanization of cassava processing. A cassava peeling machine was designed and constructed. The design parameters include a power requirement of 0.36hp belt tensions of 349.7 and 1807.5N and shaft diameter of 35mm. Its main component is a peeling chamber, which consists of two perforated drums rotating in the opposite direction. The machine had an average capacity of 44.50kg/hr, an average peeling efficiency of 83% and all average percent flesh loss of 5.38%.